REVEALING THE MEANING OF SEMIOTICS-BASED ARCHITECTURAL ART AT THE TOMB OF TEARS OF MOTHER AROSBAYA BANGKALAN - Syifauddin, Moh.; Ila Rachma, Evi Pebri; Pratama, Raga Adi (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2022)
The Tomb of Mother's Tears (Air Mata Ibu)  stands as a significant religious tourism site in Madura, housing the burial complex of Madurese nobles nestled within Buduran Village, Arosbaya District, Bangkalan Regency, on the island of Madura. Perched upon limestone hills, the nomenclature of this burial site derives from the narrative of Queen Mother Syarifah Ambami. Beyond its profound historical significance, the complex boasts a distinctive cultural architectural artistry imbued with semiotic representations of the local culture. This research endeavors to elucidate the architectural artistry of the Mother's Tears Tomb and delve into the philosophical underpinnings of this site through the lens of sociolinguistic inquiry, with a specific focus on semiotic analysis. Employing systematic linguistic research methodologies, this study aims to decipher the nuanced meanings embedded within the architectural motifs of the tomb, drawing from data gathered through field surveys and interviews conducted with tomb custodians. Through semiotic analysis, the myriad architectural motifs adorning the Mother's Tears Tomb will be examined, thereby elucidating the singular uniqueness and profound meanings encapsulated within its architectural design. The findings of this analysis and mapping endeavor promise to offer a comprehensive introduction to religious tourism in Madura, particularly in the region of Bangkalan.